Longitudinal Associations Between Perceptions of Peer Group Drinking Norms and Students' Alcohol Use Frequency Within College Sport Teams. (13th January 2020) - Graupensperger, Scott; Turrisi, Rob; Jones, Damon; Evans, M. Blair
Abstract : Background: Students' alcohol use behaviors are shaped by the attitudes and behaviors of others, especially the peers within students' proximal social groups. Explaining the association between perceived drinking norms and alcohol use, researchers propose contradicting pathways that focus on conformity (i.e., social norms predict alcohol use) and projection (i.e., alcohol use predicts perceived norms). The current study examined the extent to which conformity and projection processes were evident in the association between college student alcohol use and the perceived alcohol use norms for students' club sport teams. Methods: The sample comprised 1, 054 college students (61% female) nested in 35 intact same‐sex club sport teams. On 3 separate occasions during a single school year (3‐month lag), participants reported drinking frequency and perceptions of descriptive and injunctive group drinking norms. We employed random intercepts cross‐lagged panel modeling to estimate prospective within‐person associations separately from stable trait‐like between‐person associations. Results: Descriptive and injunctive group drinking norms were both positively related to students' alcohol use frequency at the between‐person level. Individuals nevertheless demonstrated variability at the within‐person level. Results revealed a strong contemporaneous association between descriptive norms and alcohol use frequency within each timepoint, but no prospective associations. Models including perceptions of injunctive drinking norms demonstrated similar contemporaneous associations with alcohol use frequency, but also identified significant prospective associations signifying conformity. Conclusions: Findings align with previous research reporting a strong and positive association between student's self‐reported alcohol use and subjective peer alcohol use norms. After disentangling within‐ and between‐person effects to probe for conformity and projection processes, the current findings are somewhat contrary to previous research that has reported reciprocal relationships between social norms and alcohol use behavior. Further investigation of the potential conformity and projection mechanisms of social norms is critical to advance norm‐based strategies to reduce harm. Abstract : Many have questioned whether the processes underlying the association between alcohol use and perceived social norms reflect conformity, projection, or a reciprocal association. Our findings indicated that, among sport‐playing college students, perceived injunctive drinking norms for one's sport club related to alcohol use frequency at the between‐person level and prospectively predicted alcohol use at three‐month lagged timepoints (conformity). Findings contradict existing literature, likely because of differences in normative referent group (proximal vs. distal) and use of random‐intercept cross‐lagged panel modeling.